2021
DOI: 10.3390/polym13172923
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Powder/Water Ratio Variation on Viscosity, Tear Strength and Detail Reproduction of Dental Alginate Impression Material (In Vitro and Clinical Study)

Abstract: Background: Alginate impression is a common dental polymeric material, presented as powder to be mixed with water. Aim: 1. To analyze the effect of alginate powder/water ratio variation on viscosity, tear strength and detail reproduction by in vitro tests, and 2. To evaluate this variation’s effect on patients’ impressions. Materials and methods: Two commercial alginate products were mixed in different viscosities. Viscosity was measured by a viscometer. For the tear strength test, V-shaped specimens were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
1
15
0
2
Order By: Relevance
“…As a rule of thumb, the concentration value will be greatly influenced by the molecular weight of the alginate. The higher the molecular weight, the higher the viscosity [2,14]. Previously published studies reported that the viscosity of dental impression material can be increased if the extraction of potassium alginate is carried out using freshly harvested seaweed [16,23,24].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As a rule of thumb, the concentration value will be greatly influenced by the molecular weight of the alginate. The higher the molecular weight, the higher the viscosity [2,14]. Previously published studies reported that the viscosity of dental impression material can be increased if the extraction of potassium alginate is carried out using freshly harvested seaweed [16,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Besides casting time, other factors that contribute to the accuracy and dimensional stability of irreversible hydrocolloid material are the room temperature, the water temperature of the mixture impression, the water-to-powder ratio, and the stirring intensity [1,6,11,14]. Theoretically, a warmer water temperature or general room temperature might hasten the setting time, whereas colder water will slow down the setting time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations